The Relationship between Hand Grip Strength and the Accuracy of Field Tennis Services in Eighth Semester Male Students in Department of Training Faculty of Sports Science UNIMA - Ewendi Wenik Mangolo; Fredrik Alfrets Makadada (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The aims of this study is to find out the relationship between hand grip strength and the accuracy of field tennis services. In this study the research method is quantitative research with independent variables Hand Grip Strength (X1), Sleeve Length (X2) and dependent variable Accuracy of Tennis Service (Y). The result show there is a significant relationship between hand grip strength and service accuracy in semester VII male students of the Department of Coaching Education. There is a meaningful relationship between arm length and correct service in 7th semester male students in Department of Coaching Education. There is a meaningful relationship between hand grip strength and arm length together with the accuracy of service to seventh semester male students of the Department of Training Education.